Inflammation Induces Glucocorticoid Resistance in Patients with Bronchial Asthma - Matsumura, Yasuhiro (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2009)
Glucocorticoids (GCs) represent the cornerstone of treatment of patients with bronchial asthma; however, inflammation in bronchial asthma is sometimes incompletely controlled. GCs switch on the expression of anti-inflammatory genes by binding to DNA and recruiting transcriptional coactivator molecules. In contrast, they can switch off activated inflammatory genes by recruiting transcriptional repressor molecules such as histone deacetylase (HDAC) 2. Proinflammatory transcriptional element activator protein-1 (AP-1) and transcription factor nuclear factor kappa B (NF- κB), and upstream kinase p38 and c-Jun-N-terminal kinase (JNK) amplify inflammation and resistance to the actions of GCs. The activity of histoneacetyltransferase (HAT) and HDAC influences the expression of inflammatory genes. Cytokines, inflammatory mediators, allergens, viral or bacterial infections, oxidative stress, smoking, and vitamin D deficiency may all lead to a worsened clinical outcome by influencing these pathways. Conventional therapy acts by inhibiting NF-κB, enhancing glucocorticoid receptor (GR) functions, and restoring HDAC activity, resulting in helpful add-on therapy. Targeting kinases such as inhibitor of κB kinase (IKK)2, mitogen activated protein (MAP) kinase (MAPK)s and phospho-inositol (PI)3 kinase (PI-3K) should be effective as therapy. Decoy oligonucleotides for AP-1and NF-κB are also candidates for the treatment of glucocorticoid-resistant (GC-R) asthma. Since various factors affect GC response, the pathogenesis of GC-R asthma is considered to be heterogeneous. Most GC nonresponsiveness in these patients is relative and not absolute, suggesting that resistance is dependent on the intensity of localized inflammation. A better understanding of the inflammatory mechanisms of asthma may signal the management of GC-R asthma.
Keywords: glucocorticoid receptor (GR)